The effect of repeated doses of intravenous ketamine on measures of workplace attendance and productivity in adults with major depressive and bipolar disorder: Results from the canadian rapid treatment center of excellence. (June 2021) - Rodrigues, Nelson B.; McIntyre, Roger S.; Lipsitz, Orly; Lee, Yena; Subramaniapillai, Mehala; Kratiuk, Kevin; Majeed, Amna; Nasri, Flora; Gill, Hartej; Mansur, Rodrigo B.; Rosenblat, Joshua D.
Highlights: Following 6 ketamine infusions, patients reported 2 more days of productivity. Following 6 ketamine infusions, patients reported 1.5 less days absent from work. Reduction in presenteeism was sustained following 5 months of ketamine infusions. Patients exhibited sustained antidepressant effect following 5 months of IV ketamine. Abstract: Numerous clinical trials have reported that intravenous (IV) ketamine demonstrates rapid antidepressant and anti-suicidal effects in patients with treatment-resistant depression (TRD). These studies, however, have not characterized whether these antidepressant effects translate to improvements in workplace productivity and functionality. Adults with TRD received repeated doses of IV ketamine at a community-based clinic ( n  = 171). We evaluated patient outcomes at two timepoints of interest: (1) acute-phase (i.e., following 4–6 infusions, 17.6 ± 12.6 days from baseline) and (2) maintenance-phase (i.e., following 7–10 infusions, 153.9 ± 63.4 days from baseline). The primary outcome measure was change from baseline to maintenance-phase scores on the Sheehan Disability Scale (SDS) workplace/school item as well as days underproductive (i.e., presenteeism) and days lost (i.e., absenteeism). Secondary measures included the Quick Inventory for Depression Symptomatology-Self Report 16-Item (QIDS-SR16 ). There was a significant reduction in workplace/school disability, and significantly reduced symptoms of presenteeism and absenteeism. At the acute-phase outcome, this translated to 2 more days of productivity and 1.5 less days absent from work. Additionally, IV ketamine exhibited a sustained antidepressant effect across the ten infusions. IV ketamine was associated with a significant reduction in workplace/school disability and demonstrated improvements in symptoms of presenteeism and absenteeism.